2021 IEEE International Conference on Autonomous Systems (ICAS) 2021
DOI: 10.1109/icas49788.2021.9551146
|View full text |Cite
|
Sign up to set email alerts
|

Online Unsupervised Learning For Domain Shift In Covid-19 CT Scan Datasets

Abstract: Neural networks often require large amounts of expert annotated data to train. When changes are made in the process of medical imaging, trained networks may not perform as well, and obtaining large amounts of expert annotations for each change in the imaging process can be time consuming and expensive. Online unsupervised learning is a method that has been proposed to deal with situations where there is a domain shift in incoming data, and a lack of annotations. The aim of this study is to see whether online u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Ewen et al [ 59 ] suggested online unsupervised learning approach for COVID-19-CT-scan image classification. The components of online unsupervised learning include online machine learning and unsupervised learning.…”
Section: Machine Learningmentioning
confidence: 99%
“…Ewen et al [ 59 ] suggested online unsupervised learning approach for COVID-19-CT-scan image classification. The components of online unsupervised learning include online machine learning and unsupervised learning.…”
Section: Machine Learningmentioning
confidence: 99%
“…While Online Unsupervised Domain Adaptation has been explored for other AI tasks [6,17,23,29,30,39,47], it was first defined for the field of person ReID in [33].…”
Section: Online Unsupervised Domain Adaptationmentioning
confidence: 99%